THE INFLUENCE OF PERFORMANCE MANAGEMENT AND COMPENSATION ON THE PRODUCTIVITY OF HOTEL EMPLOYEES - Ariyanto Ariyanto; Yulianah Yulianah (SEAN Institute, 2023)
The purpose of this study is to determine the simultaneous and partial effect of performance management and compensation on employee productivity. The research method used is associative research using quantitative methods. The population in this study was 300 respondents so that the research sample was 50 respondents using the slovin method. The results of the processing of multiple linear regression analysis are that performance management and compensation have a simultaneous and partial effect on the productivity of Hotel Maya Ubud Resort & Spa hotel employees. The magnitude of the influence of performance management and compensation on productivity is able to contribute as much as 64.6%.